A comparative examination of the allocation of training burdens for elite mogul skiers throughout the year - Zebzeev V.V. ,; Kurashov A.N. ,; Nosov M.S. ,; Lazarenko S.A. ,; Ilyukhin I.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to comparative examination of the allocation of training burdens for elite mogul skiers throughout the year, using data from 2021 to 2024. Methods and structure of the study. The workload of 12 top-tier Russian mogul skiers was determined through the examination of their training logs. Results and conclusions. The disparities in the metrics that describe the overall training loads in the Olympic and non-Olympic annual training cycles have been identified, and the peculiarities of the load distribution in the preparatory and competitive phases have been emphasized. The values of the loads outlined in the federal standard for sports training in freestyle significantly surpass the actual number of training sessions and time. It was discovered that the training sessions in the preparatory phase are longer in duration, while in the competitive phase they are shorter but more frequent. The Olympic annual cycle is characterized by a higher volume of specialized loads. The findings of this research can be regarded as contemporary models for periodization in the sports training of elite mogul skiers.